Weighted Implication Grid: a graph-theoretical approach to modeling psychological change construction - Sanfeliciano, Alejandro; Saúl, Luis Angel; Botella, Luis (Frontiers in Psychology, 2025)
IntroductionAnticipation and meaning-making are foundational processes in Personal Construct Psychology. Over the years, methodologies such as the Repertory Grid and Implication Grid have provided valuable tools for examining the anticipatory structure of personal meaning systems. Building on this tradition, the Weighted Implication Grid (WimpGrid) introduces a graph-theoretic and algebraic formalization of personal construct systems, aiming to enhance the modeling of psychological change as a dynamic and networked process.MethodThe WimpGrid is based on a semi-structured interview in which participants evaluate hypothetical transformations in their self-perception across a set of personal constructs. These anticipatory judgments are recorded in a numerical matrix and formalized as a weighted directed graph, where nodes represent constructs and edges quantify the perceived influence between them. From this structure, graph-theoretical indices are derived to examine properties such as construct centrality, system dynamics, and resistance to change.ApplicationsWimpGrid enables idiographic assessment in clinical settings, supporting case formulation, therapeutic planning, and longitudinal monitoring of psychological transformation. Additionally, it provides a formalized methodological platform for research into subjective change processes and personal meaning structures.DiscussionBy combining constructivist interviewing techniques with graph-theoretical modeling, WimpGrid offers a structured and flexible framework for investigating psychological change. It complements existing constructivist methodologies by providing tools for the quantitative analysis of complex meaning systems, and opens new avenues for theoretical refinement and empirical application.